Cervical neural foraminal widening caused by the tortuous vertebral artery - (:unkn) unknown (ELSEVIER SCIENCE INC, 2001)
A case of cervical neural foraminal. widening due to tortuous vertebral artery is presented. This entity is rarely seen. Plain radiography, CT, 3-D CT angiography, MRL and MRA findings of the case are presented and the importance of this vascular anomaly in the differential diagnosis of neural foraminal widening is discussed. (C) 2001 Elsevier Science Inc. All rights reserved.
Keywords: spinal neural foraminal widening; tortuous vertebral artery; CT; MR